ANOMALI PENGELOLAAN SUMBER DAYA AlAM DI TINGKAT LOKAL DALAM PERSPEKTIF EKONOMI POLITIK SASTRO M. WANTU - WANTU, SASTRO M (Jurnal Pelangi Ilmu, 2012)
Anomaly of arrangement involving the relationship of political economy and regional authorities is one of the most serious struggle that has been draining the political economic social and culture history of travel expensive in the nation of Indonesia. Arguments that can be traced from the political economic approach that the political arrangements, governance and economic character of decentralization or region autonomy, among others, the sharing or revenue and empowering localities. Especially for revenue sharing is expected to provide economic satisfaction for the region, but what happens is inequality between regions of different natural resources. Another problem area that many feel their area of interest can be enforced solely to exclusive exploration and exploitation of natural resources.